EXPERIMENTAL STUDIES OF THE RELATIONSHIP BETWEEN THE BOILING TEMPERATURE AND THE FLASH TEMPERATURE OF MIXED HYDROCARBON FUELS - Leonid P. Vogman; Stanislav G. Gabrielyan; Natalja V. Кondratyuk (Актуальные вопросы пожарной безопасности, 2021)
Based on the experiments it is shown that as the flammable liquid mixtures evaporate, while increasing density and decreasing vapor tension in multicomponent compositions-soluble, the boiling temperature increases. In this case, the flash point of the mixed combustible liquid will also increase. Thus, in the case of spills of flammable liquids there is a fairly rapid depletion of light fractions, the vapor tension at a given temperature reduces significantly, and the boiling and flash temperatures increase accordingly. The dependences of the boiling and flash temperatures of the tested mixed combustible liquids obtained in this work are also typical for other various multicomponent liquid compositions. These dependencies can be taken into account when developing plans for the prevention and elimination of emergencies caused by their spills.